CH-Diazomethane Sulfonamides Generated in Situ for Intramolecular [3+2] Cycloaddition of Alkynes: An Entry into Novel Pyrazole-Fused Five-Membered Sultams - Bubyrev, Andrey; Kantin, Grigory; Dar’in, Dmitry; Krasavin, Mikhail (Synthesis, 2021)
Previously reported CH-diazomethane sulfonamides carrying various propargylic groups are generated in situ from their acetyl precursors. Without purification, these compounds undergo a slow, albeit clean and efficient, intramolecular [3+2] cycloaddition to give pyrazole-fused five-membered sultams. The latter are the first analogues of medicinally important (hetero)arene-fused five-membered sultams containing a five-membered nitrogenous heterocycle. The newly introduced scaffold can be further elaborated into N-arylated derivatives using the Chan–Evans–Lam protocol. The resulting compounds incorporate more than one privileged moiety and are highly suitable for interrogation of protein targets via biological screening.
Keywords: diazo compounds; sultams; pyrazoles; [3+2] intramolecular cycloaddition; Mitsunobu alkylation; Chan–Evans–Lam arylation